(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3eMeO Hf eMeO Hf eUWai GdYeGOj, Gdehdi CHh GdSYhO,J (B982 (3g` s ((3eUWai GdNdhJi s)
(3ChdgG (B:s
(3ChdI JaSjQ ShQI Gdcga s
(3BNQgG (B:s
(3BNQg BNQ JaSjQ ShQI aGWQ s
(3HgG fXGe GdJYbjHIs
(3LRA efgs
(3YdjgG Jedc SfI (B1092(3g`s
(3Jedc ZjQ eDQN HGSe jhSa Hf eMeO Hf ehSi Hf YdGA GdOjf Ydi GdfSNI JbjjOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJaSjQ hYdhe GdbQBfs